Evaluation of a system for the use of methane gas as fuel for boilers at the company (Agroindustria, Sociedad y Ambiente, 2022)
In the present work, a system for the utilization of methane gas (S.A.G.M) generated in the anaerobic digestion process of vinasse was evaluated. The biogas is intended to be used as fuel in boilers of the company Destilerías Unidas S.A. (DUSA). Explanatory research and experimental design were used. The S.A.G.M. was designed at laboratory scale and consisted of an anaerobic reactor for the treatment of vinasse with a useful volume of 6 L, a solid-gas adsorption column filled with Cocos nucifera (coconut shell) epicarp, and a liquid-gas absorption column with calcium oxide (lime) solution. The efficiency of the columns was evaluated individually to know their effect on the removal of H2S and CO2, as the main pollutants of biogas when used as fuel for stationary engines. Initially, the biogas was characterized by determining the concentration of H2S and CO2 by volumetric methods, then the removal efficiency of each of the gases was evaluated by passing it through the S.A.G.M. It was obtained that the biogas contained 4.89 mg/L of H2S and 296.03 mg/L of CO2. The purification system was more effective for CO2 removal, achieving efficiencies of 95.78 and 98.16% when using the absorption and adsorption column, respectively. H2S was not significantly removed according to the hypothesis test with a 99% confidence level, due to the low initial content of this gas, the lower affinity and reaction rate of sulfides when CO2 is present. It was concluded that the biogas purified in the S.A.G.M. can be used as fuel in the company's boilers, because the remaining CO2 is negligible and the H2S concentration is below the limits recommended to feed a stationary engine.
Keywords: biogas, boiler, anaerobic digestion, methane, vinasse.